Brief Assessment of the Presence of Diatoms and Their Relationship with Some Physical and Chemical Parameters in the Pirro River, Heredia, Costa Rica - Flores-Stulzer, Eunice (2017)
The assessment of water quality in river ecosystems located in urban areas in the tropics based on the use of diatoms is scarce. This exploratory study aimed to establish the composition and species richness of diatoms in relation to physicochemical parameters as base element for monitoring the Pirro urban micro-watershed river in Heredia, Costa Rica. Materials were collected in the upper, middle, and lower river during dry, rainy, and transitional seasons. Dissolved oxygen, pH, conductivity, temperature, and composition diatomaceous were evaluated by scraping an area of 20 cm x 20 cm rocks. 18 diatom species with low abundance such as Navicula seminulum, N. minimum and N. cryptotenella were observed. These are indicatives of moderate conditions of pollution; others kinds, such as Nitzschia, display tolerant species to contaminants. The greatest diversity of species of diatoms occurred in the rainy season, and significant differences between sampling season and species richness were observed. In conclusion, Pirro river has poor sanitary conditions based on the presence of many different species, and the low channel of the river is the most affected by pollution. However, it is necessary to boost the information on this subject.